Odnaleźć swoje wewnętrzne zdanie [rec. Mark Wolynn: Nie zaczęło się od ciebie. Jak dziedziczona trauma wpływa na to, kim jesteśmy, i jak zakończyć ten proces. Przeł. M. Reimann. Warszawa: Wydawnictwo Czarna Owca, 2017, ss. 268.] - Wójtowicz-Zając, Agnieszka (Śląskie Studia Polonistyczne, 2017)
The work is a discussion of the book It Didn’t Start with You: How Inherited Family Trauma Shapes Who We Are and How to End the Cycle by Mark Wolynn, an American psychologist who deals with the therapy of inherited trauma. The author presents Wolynn’s basic assumptions regarding trauma and post-trauma and its therapeutic system and she emphasizes the popularizing aspect of the work. Afterwards, she indicates the possibilities and directions of interpretation given by Wolynn’s theory in the context of contemporary Polish prose that regards war traumas and is written by the so-called second generation.